(untitled) (Journal of the College of Education for Women, 2019)
The aim of this research is subjected to discover The Dictation mistakes which occurwidely in the Arabic Language written by Iraqi – News papers.The research classified These Mistakes in Three groups as Follows:1. The first group dealing with distinguishing between the Arabic – letter ) ا ( When Writtenor ) أ ( at The beginning The word and as ) ئ ( which differ in meaning from each other .2. The second group dealing with the writing of The Arabic ) ٙ( and as ) ٛ( at the end of Theword which differ in meaning from each other.3. The Third group dealing with distinguishing in written The Arabic letter as ) ض( or as ) )ظwhich differ in meaning From each other.4. The fourth group dealing with The writing The one Arabic – letter sometime as ) ٕ ( andother time as ) ح( which differ each other .